Menander, Theophorumenē: A Song to Kybele on the Comic Stage - Pöhlmann, Egert (Greek and Roman musical studies, 2022)
While Old Comedy abounds in musical parts, New Comedy restricts music to four act-dividing songs, about which in the papyri nothing but remarks like are transmitted. Monodies sung by actors are extremely rare. In Menander there are only two examples, a monody of a priestess in the Leukadia and a song to Kybele in the Theophoroumenē, transmitted in nine book fragments, three fragments on papyri and five mosaics depicting scenes connected with the song of the possessed girl. By integrating the book fragments and the recently enriched pictorial evidence it is possible to attempt a hypothetical reconstruction of the comedy: Menander wanted to tell the well-worn story of a foundling girl, her love affairs, rescue and marriage in a new, unexpected way by inventing the role of a girl presumably possessed by Kybele. This way he could bring a thrilling musical scene and fascinating Kybele ritual onto the stage.
CRIS-Team Scopus Importer:2022-04-22
Keywords: lyrics in Menander; music in Old and New Comedy; stock patterns in New Comedy plots; Theophoroumenē plot reconstruction; transmission of the Theophoroumenē